Propagation of Optical Signals Encrypted with Spectral Phase Encoding and Signal/Polarisation Shuffling - De Lima Cassiano Pereira, João Pedro [UNESP]; Nogueira, Marcelo Pereira [UNESP]; De Mello Fagotto, Eric Alberto; Aldaya, Ivan [UNESP]; Abbade, Marcelo Luís Francisco [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
Non-intrusive tapping and other threats have underscored the necessity for enhanced security mechanisms in transparent optical networks (TONs). In this work, we explore the application of both intra- and inter-signal cryptography techniques to secure TON signals. The intra-signal approach utilizes spectral phase encoding, while the inter-signal technique relies on shuffling the samples among different signals, including the X - and Y polarisation components of each signal. Computer simulation results suggest that encrypted 448 Gb/s dual polarisation (DP) 16-quadrature amplitude modulation (QAM) signals may be properly recovered after ∼ 700 km of standard single-mode fiber propagation.
Keywords: Network security; optical communications; signal cryptography